Initiating a complaint: Change over time in French L2 speakers’ practices - Skogmyr Marian, Klara (My University, 2021)
This study documents change over time and across proficiency levels in French second-language (L2) speakers’ practices for initiating complaints. Prior research has shown that speakers typically initiate complaints in a stepwise manner that indexes the contingent, moral, and delicate nature of the activity. Although elementary speakers in my data often launch complaint sequences in a straightforward way, they sometimes embodiedly foreshadow verbal expressions of negative stance or delay negative talk through brief positively valenced prefaces. More advanced speakers in part rely on the same initiation practices as elementary speakers. In addition, they recurrently use extensive prefatory work that accounts for and legitimizes the upcoming complaint, and they regularly initiate complaints jointly with coparticipants through a progressive escalation of negative stance expressions. I document interactional resources involved in this change and discuss the findings in terms of speakers’ development of L2 interactional competence. Data are in French with English translations.